Instructional Support for the Teaching of Critical Thinking: Looking Beyond the Red Brick Walls - Nancy Bowers (Park University, 2006)
Many instructors appreciate the importance of developing the critical thinking skills of their students yet are unfamiliar with pedagogical approaches for teaching critical thinking. These instructors rely on instructional support from teaching and learning centers or online resources. It can be time consuming, however, for instructors to translate generic teaching strategies into actual lessons related to their course content. The purpose of this paper is to review an under-utilized source of discipline-specific instructional resources for teaching critical thinking: professional organizations. Many national organizations support education within their discipline by providing a variety of instructional materials, pedagogical approaches and a venue for sharing teaching tips and lessons by their members. Hundreds of professional organizations across dozens of disciplines were examined to determine the types of instructional support provided. Representative teaching resources from these organizations are documented from a variety of disciplinary areas.